THE EFFECTIVENESS OF IN-APPLICATION PURCHASES ON MOBILE APPLICATIONS (CASE STUDY AT MOBILE GAMES APPLICATION) - Kaunang, Karenina I.; Pangemanan, Sifrid S. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: The using of in- application purchases comes with some issues along with risk because of using real money to buy virtual items, this study aims to analyze the effectiveness of in-application purchases business marketing model on mobile applications, in this case mobile games application, which is gained from consumers perception about in-application purchases. The objective of this study is to know the effectiveness of in-application purchases towards mobile games application by analyzing the consumers purchase or buying behavior. This research uses Qualitative Method with In-depth Interview, in order to know more about in-application purchases from consumers perspective. The result of this research is in-application purchases business marketing model are effective for mobile application, especially mobile games applications. This research also found that the consumers purchasing behavior are affected with social influence, hedonic motivation, and habit. For the consumer satisfaction, are determined by effort expectation, price value, and performance expectation. Based from the result gained, the consumers respond are mostly positive, and they become a loyal consumer based on the factors above, which caused an advantages for the company. From the result, the researcher recommended the company to add more various feature to the games and put age limit for purchasers. Keywords: in-application purchases, mobile applications, mobile marketing, qualitative method, consumer behavior, internet marketing, and consumer perception.